Risk Factors and Comorbidity in Childhood Specific Phobias - Abdurrahman Cahid Orengul; Yavuz Meral; Vahdet Gormez (Bilişsel Davranışçı Psikoterapi ve Araştırmalar Dergisi)
This study aims to investigate possible risk factors associated with specific phobias in children and comorbid mental disorders. Patients between 6-18 years of age who had presented to the child psychiatry outpatient clinic at Bezmialem Vakif University between October 2017 and February 2018 were assessed with The Kiddie Schedule for Affective Disorders and Schizophrenia- Present version (KSADS-P) for specific phobias and comorbid diagnoses. Risk factors of specific phobia were further evaluated with a data collection tool, developed by the authors of the present study. The most common specific phobia subtype was animal phobia (n=48; 48%), which was followed by natural environment (n=27; 27%), blood-injection (n=25; 25%), situational (n=17; 17%) and other phobia (n=2; 2%). The majority of the subjects (n=59; 63.4%) reported that specific phobias began between 3-7 years of age. While %32 percent of subjects reported a sudden onset, for 40% the onset was slow and gradual. Majority of the participants (67.7%) were not able to identify a possible trigger, whilst 25.3% reported that it started after a certain event. Only 10% of the participants had reportedly sought treatment for phobia in the past. Subjects with animal phobia or situational phobia had lower, blood/injection type phobia or natural environment type phobias had higher rates of comorbidity with an externalizing disorder as compared to the rest of the sample(Χ2=9.54, p=0.002 and Χ2=11.51, p=0.001, Χ2=6.00, p=0.014 and Χ2=8.45, p=0.004; respectively). In conclusion children and adolescents do not appear to seek help for specific phobias and such cases can be easily missed if not specifically enquired by clinicians. [JCBPR 2019; 8(2.000): 81-86]